2020
DOI: 10.9734/jpri/2020/v32i730453
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Cervical Cancer and Screening Practices among Nurses at Lahore General Hospital, Pakistan

Abstract: Objective: To find out the knowledge, awareness and screening practices of cervical cancer among nurses at Lahore general Hospital, Lahore, Pakistan. Materials and Methods: This cross-sectional, interview based study was conducted on 250 nurses at Lahore general Hospital, Lahore, Pakistan. The duration of this study was one year from 2017 to 2018. All the cases underwent interview based information regarding cervical cases. The questionnaire was applied to assess the knowledge, awareness and screening pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The current study showed that most participants (76.8%) knew that a pap smear test can detect both cancerous and precancerous lesions. This result agrees with studies done by authors Singh et al and Ayub et al [17,18]. Married nurses were more aware than unmarried women, because they are more likely to approach a health facility for obstetric, gynaecological, or other reasons, where they would be offered opportunistic screening during these visits.…”
Section: Tablesupporting
confidence: 92%
See 2 more Smart Citations
“…The current study showed that most participants (76.8%) knew that a pap smear test can detect both cancerous and precancerous lesions. This result agrees with studies done by authors Singh et al and Ayub et al [17,18]. Married nurses were more aware than unmarried women, because they are more likely to approach a health facility for obstetric, gynaecological, or other reasons, where they would be offered opportunistic screening during these visits.…”
Section: Tablesupporting
confidence: 92%
“…This result is supported by other studies reporting that the participants were aged between 26 and 30 years and were married (61.7%) [17], ages of samples were between 26 and 40 years, and a majority (90%) of them were married [16]. In a cross-sectional study by Ayub in Pakistan among nursing staff, their ages were between 25-34, and more than two-thirds of nurses (72%) were married [18]. Another result agrees with the present study, which was done in an institution in rural India by Shekhar among nursing staff their age was between (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and most of them (86.6%) were married [19].…”
Section: Tablesupporting
confidence: 73%
See 1 more Smart Citation
“…31 Inadequacy of knowledge is not restricted to any segment, but it prevails all across the demographic in our population regardless of professor and education level. [32][33][34] Our study has certain limitations. Single-center coverage with a relatively small sample size can be the main limitation toward the generalizability of our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…31 Inadequacy of knowledge is not restricted to any segment, but it prevails all across the demographic in our population regardless of professor and education level. 32 33 34…”
Section: Discussionmentioning
confidence: 99%